THE AFTERMATH OF COVID-19 ON STUDENTS’ EDUCATION AND HEALTH IN INDIAN EDUCATIONAL INSTITUTIONS: A SURVEY - Mann, Pooja; Mann, Bhoomika (Journal of Education Culture and Society, 2021)
Aim. This paper aims to bring forth how the basic right of education got adversely affected due to the COVID-19 pandemic. The unplanned and immediate shift to online classes adversely affected the students’ physical and mental health as several issues that the students faced were related to the lack of adequate resources. Methods. The data for this paper were collected through a self-prepared and structured questionnaire, using Google forms, which was then circulated among different stakeholders of the educational institutes. The statistical analysis of the collected data was done using Microsoft Excel. Results and conclusion. According to the analysis of the survey, smartphones (75% of the total respondents) are relatively more accessible by students in comparison to computers or laptops (53%). And even if students had internet connectivity (57%), they faced issues of low data bandwidth (39%) leading to poor quality of online interaction in classes. Another important analysis suggested that 57% of students lacked a quiet room or space to attend the online classes in their homes. Finally, the negative impacts of online classes on the physical and mental health of students were also analysed. Cognitive value. The findings and the analysis of this paper would thus help teachers and institutions to understand students’ views and experiences of the pandemic. This understanding would help teachers to plan their teaching plans accordingly bridging the digital divide which would help students learn and grow.